DETERMINAN NILAI PERUSAHAAN SEKTOR KESEHATAN DI INDONESIA: DETERMINANTS OF FIRM VALUE OF HEALTHCARE SECTOR IN INDONESIA - Maylani, Rhizma Putri; Oktafiyani, Melati; Prajanto, Agung (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
The study investigates the effect of financial performance (profitability, liquidity, and solvency) on firm value. The methodology employs a quantitative approach, utilizing secondary data from annual reports. The research focuses on healthcare sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The study utilized purposive sampling methods to observe 98 company samples. The study employs multiple linear regression analysis to conduct hypothesis testing with IBM SPSS version 26 software. The analysis indicates that profitability significantly enhances the value of a firm. Liquidity significantly enhances the firm's value. The statement suggests that the effect of solvency on firm value is not significant. The contribution of this research is to provide information for investors in assessing companies in the healthcare sector to consider the importance of financial performance so that it can be used as a reference in making investment decisions, as well as provides insights for regulators in designing stategies to support the sustainable increase the value of healthcare sector companies in a competitive market.